2021
DOI: 10.1001/jamanetworkopen.2021.40732
|View full text |Cite
|
Sign up to set email alerts
|

School and Work Absences After Critical Care Hospitalization for Pediatric Acute Respiratory Failure

Abstract: Key Points Question How often and for how long do children and their caregivers miss school or work after critical care hospitalization for acute respiratory failure? Findings In this secondary analysis of the Randomized Evaluation of Sedation Titration for Respiratory Failure clinical trial, more than two-thirds of children missed school after discharge for a median of 9.1 days. Among primary caregivers, more than half missed work after their child’s hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…10 Two thirds of children miss school after hospital discharge following critical illness, missing a median 9 days of school. 11 Up to 20% do not return to school at all within 3 months following hospital discharge; those who do return have lower self-reported school functioning compared to healthy, agematched controls. 12 Critical illness frequently affects family social health, through changes in parental employment, housing, other economic resources, and parents' mental and social wellbeing.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…10 Two thirds of children miss school after hospital discharge following critical illness, missing a median 9 days of school. 11 Up to 20% do not return to school at all within 3 months following hospital discharge; those who do return have lower self-reported school functioning compared to healthy, agematched controls. 12 Critical illness frequently affects family social health, through changes in parental employment, housing, other economic resources, and parents' mental and social wellbeing.…”
Section: Introductionmentioning
confidence: 98%
“…12 Critical illness frequently affects family social health, through changes in parental employment, housing, other economic resources, and parents' mental and social wellbeing. 11,[13][14][15] These examples suggest that social health after critical illness involves interpersonal relationships, participation in age-appropriate social roles and activities, and the social context of family and community environments. Unfortunately, pediatric critical care outcomes research has inconsistently defined social health and its measurements (referred to in this manuscript as social outcomes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carlton and colleagues 1 found that after hospital discharge, 70% of children were absent from a preschool, daycare, or school at which they were previously enrolled. These absences were for a median (IQR) of 16.9 (7.9-43.9) days and are in addition to a median hospital length of stay of 2 weeks (10 school days) and any prehospital absences.…”
mentioning
confidence: 99%
“…Pediatric critical illness can be highly disruptive, both during and after admission to a pediatric intensive care unit (PICU). The study by Carlton et al provides an important advance in the knowledge about the consequences of critical illness for patients, their siblings, and their caregivers. Carlton et al report a secondary analysis of data from the Randomized Evaluation of Sedation Titration for Respiratory Failure (RESTORE) cluster randomized clinical trial of protocolized sedation vs usual care for children with respiratory disease receiving mechanical ventilation.…”
mentioning
confidence: 99%